2012
DOI: 10.1590/s0100-29452012000300041
|View full text |Cite
|
Sign up to set email alerts
|

Subenxertia da goiabeira 'Paluma' com araçazeiros resistentes a Meloidogyne enterolobii (sin. M. mayaguensis)

Abstract: , GRAziELLA siqUEiRA CAMPos 5 RESUMO -Estudos anteriores demonstraram resistência ou imunidade ao nematoide Meloidogyne enterolobii em araçazeiros (Psidium cattleyanum sabine), mas não foi encontrada essa resistência em goiabeiras. o objetivo deste trabalho foi avaliar a subenxertia entre a goiabeira 'Paluma' e araçazeiros, como um meio de obter goiabeiras resistentes ao nematoide. oitenta plântulas da goiabeira 'Paluma', produzidas por estaquia, foram conduzidas em vasos de 5 litros (uma por vaso) até que ati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…'Paluma' and the rootstocks of guava reaching 63,3% while grafting success between Paluma and cattley guava plants from accessions 115 and 117, reaching 32 and 29%, respectively. ROBAINA et al (2012) observed low rates of inarching success between of P. guajava 'Paluma' and accessions 115 and 117. The authors suggest incompatibility between the tissues of guava and of these accessions.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…'Paluma' and the rootstocks of guava reaching 63,3% while grafting success between Paluma and cattley guava plants from accessions 115 and 117, reaching 32 and 29%, respectively. ROBAINA et al (2012) observed low rates of inarching success between of P. guajava 'Paluma' and accessions 115 and 117. The authors suggest incompatibility between the tissues of guava and of these accessions.…”
Section: Resultsmentioning
confidence: 80%
“…'Paluma'. ROBAINA et al (2012) assessed the fixation of inarching and did not observe survival of P. guajava 'Paluma' inarching with accession 116, either. The inarching using accession 116 of cattle guava presented tissue welding with guava, but the lack of functionality of the vascular tissues was observed.…”
Section: Resultsmentioning
confidence: 93%
“…When evaluating inarching under the canopy of 'Paluma' guava, Robaina et al (2012) found success percentage of 40% when the sub-graft used was of the same species (intraspecific), and between 0 and 20% when using Psidium cattleyanum subgraft (interspecific). In the work above, the lower grafting success percentage verified was associated to the lack of compatibility between the tissues of the two species.…”
Section: Resultsmentioning
confidence: 98%
“…Brazil is one of the world's largest producers of guava and its cultivation is distributed throughout the country (ROZANE et al, 2009). The introduction of this crop in irrigated areas of Pernambuco and Bahia states in 1985 diversified the semi-arid region potential to meet both national consumption and exportation, allowing the production of highquality fruits over the year (FLORI and CASTRO, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In order to make viable the use of genetic resistance, the compatibility of araçá rootstocks for 'Paluma' scions has been tested (CARNEIRO et al, 2007;ALMEIDA et al, 2009). Although it proved its feasibility, in some cases a lack of compatibility in araçá inarches has also been reported (ROBAINA et al, 2012). At the same time, studies that clarify the mechanisms involved in the response of Psidium species to nematodes are necessary for a longer duration and effectiveness of the adopted management strategies.…”
Section: Introductionmentioning
confidence: 99%